Administrative-Territorial Reform: The Experience of the Countries of Western Europe - Harust, Yuriy; Durnov, Yevhen; Boichuk, Andrii; Chernezhenko, Olena; Holosnichenko, Ivan (Cuestiones Políticas, 2020)
The relevance of this article is conditioned by the decentralization of the reform of political power in Ukraine, which presents the State with the permanent challenge of finding new ways to solve the problems of governance and governability at the district and regional level. The objective of the article was to carry out a scientific investigation on the mechanism of introduction of institutes of prefects in Ukraine, based on the experience of the main western European countries. The main research methods are general and specific, including the methods of logic, analysis and comparison of the sources consulted. The results of this study are to identify ways to introduce an institute of prefects in Ukraine. By way of conclusion, it highlights the importance of the results obtained, which is reflected in the fact that this study can serve as a basis to delineate future changes to the current legislation of Ukraine on issues of state administration, at the district and regional level, by introducing the institute of prefects.